RECONSTRUCTION REGULATION OF AUTHORITY OF LEGISLATIVE MEMBER IN PREVENTING CRIMINAL CRIMINAL ACCOUNT BASED ON JUSTICE VALUES - wandi subroto (Jurnal Pembaharuan Hukum, 2017)
The House of Representatives is a central legislative body that represents the people in parliament. The authority of each legislative member and as an institution has been regulated by legislation. The authority of the House of Representatives as an institution is huge, and the great power tends to be misused, such as committing a criminal act of corruption. Corruption is a crime that is very detrimental to the state's finances and hinders the government to prosper its people, then a justice-based arrangement is needed to prevent corruption within The House of Repre-sentatives as a legislative body.